Peningkatan Hasil Belajar Siswa Kelas III SD Inpres IV dengan Metode Jarimatika Penjumlahan Bersusun - Tiffany Shahnaz Rusli; Chelsi Yuliana; Hidayah Hidayah (STKIP Andi Matappa Pangkep, 2023)
The aim of this research is to increase the knowledge of class III students at SD Negeri Inpres Perumnas regarding the material of compound addition using the material of compound addition using the Jarimatika method. Classroom Action Research (PTK), which was carried out in two cycles. The results of the study showed that using Jarimatika significantly increased students' understanding of compound addition material. The students average score increased from 65 to 78 during the first cycle and to 88 during the second cycle. The results of this research show that the Jarimatika method is effective in improving student learning outcomes and making mathematics learning more interesting and interactive. This method can be recommended for use in teaching mathematics at elementary school level.